Plastic hinge length of shape memory alloy (SMA) reinforced concrete bridge pier. (15th June 2016) - Billah, A.H.M. Muntasir; Shahria Alam, M.
Highlights: A well calibrated finite element model was developed and verified against test results. Effect of different parameters on plastic hinge length was investigated. Strain profile and curvature profile was used for deriving the plastic hinge length expression. A new equation was proposed for predicting the plastic hinge length of SMA-RC bridge pier. Plastic hinge length of SMA-RC pier increases as the axial load, aspect ratio and the yield strength of SMA rebar increases. Abstract: It is often assumed that the maximum seismic damage in a bridge pier will concentrate in the regions subjected to maximum inelastic curvature known as its plastic hinge length. Predicting the plastic hinge length accurately is an important part of seismic design of bridge piers. This study focuses on deriving an analytical expression for the plastic hinge length of shape memory alloy (SMA) reinforced concrete (RC) bridge pier based on the results from well calibrated nonlinear finite element models. A parametric study was performed to investigate the effect of different parameters on the plastic hinge length, including axial load ratio, aspect ratio, concrete strength, SMA properties, longitudinal and transverse reinforcement ratio. Multivariate regression analysis was performed to develop an expression to estimate the plastic hinge length in SMA-RC bridge pier. The results are compared with the existing plastic hinge length equations. The proposed equation was validated against test results which showed reasonable accuracy.